Chromosome walking and gene cloning using a Neurospora crassa Linkage Group VI-specific library. - Thomas J Schmidhauser (Fungal Genetics Reports, 1999)
Chromosome walks from the cpc-1 and Bml loci were extended and the cys-2 locus cloned by sib-selection using a subset of the Orbach/Sachs Neurospora crassa genomic library.